Synthesis of aqueous AgInS/ZnS@PEI as a self-indicating nonviral vector for plasmid DNA self-tracking delivery. Issue 43 (1st October 2015) - Yang, Wentao; Guo, Weisheng; Zhang, Tingbin; Yang, Weitao; Su, Lin; Fang, Lei; Wang, Hanjie; Gong, Xiaoqun; Chang, Jin
Abstract : Synthesis of aqueous ZAIS@PEI QDs as versatile self-tracking gene vectors, allowing the real-time monitoring of gene transfection behavior in live cells without external fluorescence labeling. Abstract : Various nanoparticles have been employed for gene delivery. Revealing the endocytosis or phagocytosis behaviors of the gene delivery system is critical for designing sophisticated gene therapies. Herein, a kind of water-soluble PEI capped AgInS/ZnS (ZAIS@PEI) quantum dot was synthesized as a self-indicating gene vector in the presence of branched polyethylenimine (PEI) and mercaptopropionic acid (MPA). The as-prepared ZAIS@PEI QDs could efficiently condense plasmid DNA into nanocomplexes with strong fluorescence, which can reveal their positions during gene transfection. Our results confirmed that ZAIS@PEI could mediate plasmid DNA delivery into HeLa cells with the high transfection efficiency of 40% and low cytotoxicity, meanwhile allowing the real-time monitoring of gene transfection. The obtained ZAIS@PEI QDs were verified as versatile self-tracking gene vectors, which integrated gene delivery with bioimaging functions without external labeling.